Design Modification of the Measuring Unit for Detecting Temperatures and Speeds on the UIC Flywheel Test Stand (Current Problems in Rail Vehicles, 2021)
The article deals with the design of the measuring unit used to determine the temperatures and speeds, which is used on the flywheel state of the UIC. The measurement of the speed of a railway wheel or a brake disc can be performed by two independent measuring methods. One of the methods proved ineffective. Therefore, it was necessary to make a structural modification to the connection of the ring head, which is used for measuring temperatures by means of thermocouples, in order to be able to connect a speed sensor to it in series.
Keywords: break test stand; temperature; speed